Propulsion system design of rigid tube rib / Faiz Syazwan Zulkifli - Zulkifli, Faiz Syazwan (2022)
Rigid Inflatable Boats RIB are the ideal form of boat for first rescuers, search and rescue teams, and all other rescue professionals due to the numerous advantages they provide over traditional boats. However, the cost of material was high and only can afford by rescue team from government. This project is to innovate some part of the boat to reduce the cost and make it affordable. So that, everyone can have their own boat for safety feature or use it for recreational activities. Rigid Inflatable Boat RIB are using Teflon material for the inflatable part. This project replaces Teflon with PVC because it cheaper. However, the design of the boat must be followed by PVC structure. Other than that, engine power needs to be upgraded to increase the propulsion power because the PVC material is heavier than Teflon.